A study on phytochemical profiling of Avicennia marina mangrove leaves collected from Indian Sundarbans - Sayantani Mitra; Nabanita Naskar; Susanta Lahiri; Punarbasu Chaudhuri (Sustainable Chemistry for the Environment, 2023)
Mangroves are the most diverse and productive ecosystem that is enriched with various classes of phytochemicals having potential medicinal applications. Here we have studied the bioactive potential and the presence of secondary metabolites in Avicennia marina, one of the dominant species in the Indian Sundarbans mangrove habitat. The bioactive potential study of A. marina was carried out in terms of the determination of total phenolic content, total flavonoid content and reactive oxygen species scavenging potential. The methanolic and ethyl acetate extracts were subjected to Fourier transform infrared spectroscopy (FTIR) for functional group identification. Further, detailed phytochemical profiling has been carried out by liquid chromatography-mass spectrometry (LC-MS). The Total Phenolic Content (TPC) and Total Flavonoid Content (TFC) values for the methanolic extract of A. marina leaves were 148.0 mg GAE g−1 dry extract and 251.9 mg CE g−1 dry extract which was higher than ethyl acetate extracts. The free radical scavenging potential showed that methanolic extract of A. marina leaves can scavenge DPPH (1,1-diphenyl-2-picrylhydrazyl) free radical up to 96.0 % and ethyl acetate extract can scavenge up to 73.7 % at 250 µg mL−1. LC-MS metabolic profile revealed the presence of different classes of secondary metabolites like fatty acids, flavonoids, plant hormones, etc., in methanolic extract. The presence of different classes of phytochemicals in the methanolic extract proves its potential as a source of plant-derived medicinal compounds.